Peran Perhatian Orang Tua dalam Pengaruh Kecerdasan Adversitas dan Efikasi Diri Terhadap Hasil Belajar Ekonomi Siswa Kelas XI Soshum SMAN Se-Kabupaten Tana Tidung - Arbayati, Arbayati; Wahyuni, Daru; Robi, La (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the influence of adversity intelligence and self-efficacy on students' economic learning outcomes, as well as to evaluate the role of parental attention as a moderating variable. This study employs a quantitative approach with an associative-causal design, involving 145 Grade XI Social Sciences students from three public high schools in Tana Tidung Regency. The research instruments include questionnaires and academic achievement tests, analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that adversity intelligence (β = 0.377; p = 0.007) and self-efficacy (β = 0.353; p = 0.001) have a positive and significant effect on academic achievement. Additionally, parental attention was found to significantly moderate the relationship between adversity intelligence (β = 0.24; p = 0.001) and self-efficacy (β = 0.22; p = 0.001) on students' academic achievement. The increase in the coefficient of determination from R² = 0.070 to R² = 0.086 after moderation indicates that parental attention strengthens the relationship between internal psychological factors and academic achievement. These findings emphasize the importance of collaboration between strengthening students' psychological resilience and parental involvement in supporting learning success, especially in areas with limited access to education.